2012
DOI: 10.1002/cctc.201200175
|View full text |Cite
|
Sign up to set email alerts
|

High‐Surface‐Area SiO2–ZrO2 Mixed Oxides as Catalysts for the Friedel–Crafts‐Type Alkylation of Arenes with Alcohols and Tandem Cyclopropanation Reactions

Abstract: The catalytic activity of SiO2–ZrO2 mixed oxides was studied for the Friedel–Crafts‐alkylation reaction between anisole and benzylic or allylic alcohols. In particular, the influence of Zr content on the catalytic activity was studied. The catalyst with the lowest Zr content (5 mol % ZrO2) showed the highest activity with high selectivity for the alkylated product and good recyclability. We used this catalyst in the reaction of 1‐phenyl‐1‐ethanol with toluene and xylene. We also studied the possibility of a ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…A comparison of the properties and activities of some NHSG [48] and conventional SiO 2 -TiO 2 catalysts shows that NHSG samples give comparable or better results (Table 2). SiO 2 -ZrO 2 oxides prepared by NHSG reactions were reported as catalysts for Friedel-Crafts alkylation [210], MPV reduction [50], and aminolysis reactions [50]. Kaper et al reported a high surface area (up to 570 m 2 ·g −1 ) zirconium silicate catalyst prepared by alkyl halide elimination [210].…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison of the properties and activities of some NHSG [48] and conventional SiO 2 -TiO 2 catalysts shows that NHSG samples give comparable or better results (Table 2). SiO 2 -ZrO 2 oxides prepared by NHSG reactions were reported as catalysts for Friedel-Crafts alkylation [210], MPV reduction [50], and aminolysis reactions [50]. Kaper et al reported a high surface area (up to 570 m 2 ·g −1 ) zirconium silicate catalyst prepared by alkyl halide elimination [210].…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
“…SiO 2 -ZrO 2 oxides prepared by NHSG reactions were reported as catalysts for Friedel-Crafts alkylation [210], MPV reduction [50], and aminolysis reactions [50]. Kaper et al reported a high surface area (up to 570 m 2 ·g −1 ) zirconium silicate catalyst prepared by alkyl halide elimination [210]. The resulting material exhibited high catalytic activity for Friedel-Crafts alkylation reactions between anisole and various alcohols.…”
Section: Heterogeneous Catalystsmentioning
confidence: 99%
“…Of particular interested is the result obtained when (E)-1,3-diphenylprop-2en-1-ol (3) was reacted at 110 °C with benzyl alcohol as the solvent. The desired result was an intramolecular Friedel-Crafts reaction and subsequent transfer hydrogenation (MPV-type) of the double bond to obtain the product 10, but instead the major product was the cyclopropane derivative 11, the result of the hydrogenation of cyclopropene 12 [Scheme 16,(b)] 32.…”
mentioning
confidence: 99%
“…Common aliphatic alcohols, such as cyclohexanol and 1-hexanol, were also tested, but no reaction occurred under the standard reaction condition (Table 3, Entries 3 and 4). This was probably attributed to the inert nature of these primary and secondary alcohols for the FC reaction, which were also mentioned in the reported literature [15]. In particular, alkyl halide benzyl bromide was also tested as an electrophile, which provided 99.1% of the target product under optimal reaction conditions, indicating the broad applicability of the Hf/SBA-15(20) catalyst in the FC reaction (Table 3, Entry 5).…”
Section: Resultsmentioning
confidence: 54%
“…For example, Lingaiah et al [13] reported tin-exchanged heteropoly tungstate was successfully applied to the benzylation of arenes with benzyl alcohol and almost full conversion and quantitative products were obtained at 393 K of reaction temperature. Sugi et al [14] reported the rare earth metal triflates (e.g., Sc(OTf) 3 , Hf(OTf) 3 ) supported on MCM-41 for FC reactions and over a 90% yield of target products could be obtained at 353 K. Kaper et al [15] reported the use of mixed oxide SiO 2 -ZrO 2 for the FC alkylation of anisole and benzylic or allylic alcohols and they claimed the importance of creating a mesoporous structure of the catalysts, which enabled better mass diffusion during the reaction. Of all these solid catalysts, mesoporous Lewis type catalysts are more promising and practical for FC reaction in terms of their high reaction efficiency, better thermal stability, and recyclability.…”
Section: Introductionmentioning
confidence: 99%